THE IMPORTANCE OF MARKETING AND MARKETING STRATEGY IN THE DEVELOPMENT OF COMPANIES (International journal of artificial intelligence, 2025)
Marketing plays a pivotal role in the growth and sustainability of companies in an increasingly competitive business environment. A well-defined marketing strategy helps businesses identify target markets, understand customer needs, and position their products or services effectively. This paper explores the significance of marketing in company development, focusing on how strategic marketing approaches drive brand awareness, customer engagement, and revenue growth. The study also highlights key marketing strategies, including digital marketing, content marketing, and customer relationship management, which contribute to long-term business success.